Inflammatory Myofibroblastic Tumor of the Anus: A Case Report - Tetsuyoshi Takayama; Ayako Nakame; Masaomi Suzuki; Hiroshi Asano; Ling Jin (Journal of the Anus, Rectum and Colon, 2024)
Inflammatory myofibroblastic tumors (IMTs) are neoplastic lesions characterized by the proliferation of spindle cells with myofibroblastic features and lymphocyte infiltration. Primary lesions can develop in several locations but rarely arise in the colon as described herein. The present case was that of a 69-year-old woman who visited our hospital with complaints of bloody bowel discharge and a prolapsed mass from the anus. A 20-mm tumor was identified on visual and digital examination. Lower gastrointestinal endoscopy revealed a pedunculated, elevated lesion above the dentate line, which showed contrast enhancement on abdominal computed tomography. The patient was preoperatively diagnosed with an anal polyp, which was resected transanally. During the procedure, a mobile tumor coated by anal epithelium was observed at the 11 o'clock position above the dentate line. Deeper parts of the tumor were contiguous with the internal anal sphincter (IAS) muscle. Suspecting a neoplastic lesion, we resected the mass en bloc with part of the IAS. Tumor histopathology after surgery led to a final diagnosis of an IMT of the anus. IMT is difficult to diagnose preoperatively. No adjuvant therapy has been formally established; thus, an adequate surgical margin and close monitoring are essential.